Interactions between PPAR Gamma and the Canonical Wnt/Beta-Catenin Pathway in Type 2 Diabetes and Colon Cancer - Yves Lecarpentier; Victor Claes; Alexandre Vallée; Jean-Louis Hébert (PPAR Research)
In both colon cancer and type 2 diabetes, metabolic changes induced by upregulation of the Wnt/beta-catenin signaling and downregulation of peroxisome proliferator-activated receptor gamma (PPAR gamma) may help account for the frequent association of these two diseases. In both diseases, PPAR gamma is downregulated while the canonical Wnt/beta-catenin pathway is upregulated. In colon cancer, upregulation of the canonical Wnt system induces activation of pyruvate dehydrogenase kinase and deactivation of the pyruvate dehydrogenase complex. As a result, a large part of cytosolic pyruvate is converted into lactate through activation of lactate dehydrogenase. Lactate is extruded out of the cell by means of activation of monocarboxylate lactate transporter-1. This phenomenon is called Warburg effect. PPAR gamma agonists induce beta-catenin inhibition, while inhibition of the canonical Wnt/beta-catenin pathway activates PPAR gamma.